Effect of Ciprofloxacin on Some Oxidative Stress Parameters and TNF-α, IL-6 and BDNF in Diabetic Rats with Urinary Tract İnfection Induced by Escherichia coli - Akman, Nur; Komuroglu, Ahmet Ufuk (Indian Journal of Pharmaceutical Education and Research)
Background: Diabetes Mellitus (DM) and Urinary Tract Infections (UTIs) are common conditions that, especially when occurring together, lead to significant morbidity. This study aimed to investigate the effects of Ciprofloxacin (CIP) treatment on oxidative stress, antioxidant defense systems, and inflammatory markers in a rat model of experimental DM and E. coli-induced UTI. Materials and Methods: The study was conducted on rats with experimental DM and E. coli-induced UTI. CIP treatment was administered, and oxidative stress markers, antioxidant defense systems (including Catalase (CAT) and Glutathione (GSH) activity), and inflammatory markers (such as Malondialdehyde (MDA) and Advanced Oxidation Protein Products (AOPP)) were assessed in both serum and brain tissue. Brain-Derived Neurotrophic Factor (BDNF) levels were also measured. Results: The combination of DM and UTI significantly increased oxidative stress in both serum and brain tissues, as evidenced by elevated MDA levels (p<0.05), decreased CAT and GSH activities (p<0.05), and increased AOPP levels (p<0.05). CIP treatment significantly reduced serum MDA levels in both DM and DM+UTI groups, but did not result in significant improvements in CAT, GSH, or AOPP levels. In brain tissue, however, CIP treatment negatively affected MDA, GSH, CAT, and AOPP levels, particularly in the DM+UTI group (p<0.05). Additionally, CIP treatment led to an increase in BDNF levels (p<0.05) in brain tissue. Conclusion: While CIP treatment may alleviate oxidative damage in serum, it may exacerbate oxidative stress and inflammatory responses in brain tissue, particularly in the DM+UTI model. The increase in BDNF levels could act as a survival mechanism in response to CIP-induced oxidative damage. These findings suggest that CIP treatment may have undesirable neurological effects in DM and DM+UTI, emphasizing the need for further research into its impact on the nervous system. In conclusion, this study highlights the potential for CIP treatment to lead to undesirable neurological effects in DM and DM+UTI and emphasizes the need for further research into its impact on the nervous system.
Keywords: BDNF; Ciprofloxacin; Diabetüs Mellitüs; Oxidative Stress.